2018
DOI: 10.1007/s00104-018-0648-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation zur Infrastruktur für klinisch chirurgische Studien in Deutschland

Abstract: The hospitals that participate in CHIR-Net structures were superior to hospitals that do not participate in CHIR-Net structures regarding study activity, infrastructure for clinical trials, study-specific education of clinicians, grant applications and publication rates. The goal of the grant was achieved and the funding led to manifold, long-term cooperation and a clear improvement of the study culture in surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another drawback-at least in Germany-prohibiting the ideas of a national study society that conducts clinical trials is that the funding criteria allow a funding only at public health facilities, and an independent organization is exempt from this [33]. Initiatives such as the National Surgical Trial Network (CHIR-Net), which have been trying for many years with great commitment and enthusiasm to promote cooperation between the centres and to increase the study quality and funding application approval rate, have not yet been able to exploit their outstanding potential due to a lack of financial, personal and organizational support [34][35][36].…”
Section: Study Culture In Surgery In Germanymentioning
confidence: 99%
“…Another drawback-at least in Germany-prohibiting the ideas of a national study society that conducts clinical trials is that the funding criteria allow a funding only at public health facilities, and an independent organization is exempt from this [33]. Initiatives such as the National Surgical Trial Network (CHIR-Net), which have been trying for many years with great commitment and enthusiasm to promote cooperation between the centres and to increase the study quality and funding application approval rate, have not yet been able to exploit their outstanding potential due to a lack of financial, personal and organizational support [34][35][36].…”
Section: Study Culture In Surgery In Germanymentioning
confidence: 99%
“…Thus, a network was started to initiate and coordinate surgical research in Germany to overcome this development (31) by providing services to ease research activities and to help in knowledge transfer to non-academic centers (32). The efficacy of this network has been evaluated by comparing participating to non-participating hospitals and found that participating hospitals have more personal formally qualified in conducting clinical research, more often qualify their doctors to become a clinical investigator, participate in more multicenter trials, and have more supporting infrastructure (33), thus improving scientific quality and quantity of surgical research in Germany (32,33).…”
Section: A Similar Situation In General Surgerymentioning
confidence: 99%